Data and R-scripts from: Multiple stressors: negative effects of nest predation on the viability of a threatened gull in different environmental conditions - Bårdsen, Bård-Jørgen; Bustnes, Jan Ove (Zenodo, 2022)
This contains data and R-scripts used in: Bård-Jørgen Bårdsen and Jan Ove Bustnes (2022). Multiple stressors: negative effects of nest predation on the viability of a threatened gull in different environmental conditions. Journal of Avian Biology. This study assessed the population viability of a population of the lesser black-backed gull ( Larus fuscus fuscus ) using data collected during 2005-2020 from a nature reserve in Northern Norway. The study merged results from statistical analyses of empirical data with a Leslie model. Here, we provide the underlying data, and the R-scripts used to analyse the data and run the model. The data set include information about reproduction at several stages (laying, hatching and fledgling), nest predation, and individual capture histories (used to estimate apparent survival; see Bårdsen and Bustnes 2022 ). Data Our study area, located within the Horsvær Nature Reserve in Northern Norway (65°19′N 11°38′E), is one of several key sites within the Norwegian seabird monitoring program ( SEAPOP ). We view the uploaded data as a means to verify the results presented in our article ( Bårdsen and Bustnes 2022 ). The data available here terminated in 2019 (reproduction and nest predation) and 2020 (apparent survival). All the data is available in 'ToBePublished.zip' (downloadable software). Still, we upload the data from our study area as a separate file ('Data.zip') for those interested in the data without the scripts. You may contact Jan Ove Bustnes ( jan.bustnes@nina.no ), responsible for the Horsvær key site if you have any inquiries regarding the data from our study area. If you choose to use the uploaded data, we would appreciate the following: Please acknowledge the persons who contributed to the data collection: Harald Bustnes, Sigfred Jørgensen and Runar Omnø for logistical support; Trond Vidar Johnsen, Morten Helberg, Klaus Maløya Torland, Nils Helge Lorentzen, Kjetil Olsen, Geir Arne Bustnes and Jorg Welcker for field assistance. Please cite Bårdsen and Bustnes ( 2022 ) ...